Photoprotective Properties of Isothiocyanate and Nitrile Glucosinolate Derivatives From Meadowfoam (Limnanthes alba) Against UVB Irradiation in Human Skin Equivalent - Carpenter, Evan L.; Le, Mai N.; Miranda, Cristobal L.; Reed, Ralph L.; Stevens, Jan F.; Indra, Arup K.; Ganguli-Indra, Gitali (Frontiers in Pharmacology, 2018)
Exposure to ultraviolet B (UVB) irradiation of the skin leads to numerous dermatological concerns including skin cancer and accelerated aging. Natural product glucosinolate derivatives, like sulforaphane, have been shown to exhibit chemopreventive and photoprotective properties. In this study, we examined meadowfoam (Limnanthes alba) glucosinolate derivatives, 3-methoxybenzyl isothiocyanate (MBITC) and 3-methoxyphenyl acetonitrile (MPACN), for their activity in protecting against the consequences of UV exposure. To that end, we have exposed human primary epidermal keratinocytes (HPEKs) and 3D human skin reconstructed in vitro (EpiDermTM FT-400) to UVB insult and investigated whether MBITC and MPACN treatment ameliorated the harmful effects of UVB damage. Activity was determined by the compounds’ efficacy in counteracting UVB-induced DNA damage, matrix-metalloproteinase (MMP) expression, and proliferation. We found that in monolayer cultures of HPEK, MBITC and MPACN did not protect against a UVB-induced loss in proliferation and MBITC itself inhibited cell proliferation. However, in human reconstructed skin-equivalents, MBITC and MPACN decrease epidermal cyclobutane pyrimidine dimers (CPDs) and significantly reduce total phosphorylated γH2A.X levels. Both MBITC and MPACN inhibit UVB-induced MMP-1 and MMP-3 expression indicating their role to prevent photoaging. Both compounds, and MPACN in particular, showed activity against UVB-induced proliferation as indicated by fewer epidermal PCNA+ cells and prevented UVB-induced hyperplasia as determined by a reduction in reconstructed skin epidermal thickness (ET). These data demonstrate that MBITC and MPACN exhibit promising anti-photocarcinogenic and anti-photoaging properties in the skin microenvironment and could be used for therapeutic interventions.